2017
DOI: 10.1186/s12858-017-0076-2
|View full text |Cite
|
Sign up to set email alerts
|

Copper chelation and interleukin-6 proinflammatory cytokine effects on expression of different proteins involved in iron metabolism in HepG2 cell line

Abstract: BackgroundIn vertebrates, there is an intimate relationship between copper and iron homeostasis. Copper deficiency, which leads to a defect in ceruloplasmin enzymatic activity, has a strong effect on iron homeostasis resulting in cellular iron retention. Much is known about the mechanisms underlying cellular iron retention under “normal” conditions, however, less is known about the effect of copper deficiency during inflammation.ResultsWe show that copper deficiency and the inflammatory cytokine interleukin-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 91 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, liver copper levels were increased in adjuvant-induced arthritis in rats during the inflammatory process (68). Another study demonstrated that elevated IL-6 levels resulted in increased levels of ceruloplasmin, the major copper-carrying protein in the blood (69).Therefore, the increase in copper levels could be related to the body's physiological reaction to fight inflammation (68). In addition, the inflammatory disease may be the result of insufficient hepatic copper repositories that cannot support an anti-inflammatory response (70).…”
Section: Prodrug Of β-D-n4-hydroxycytidine (Eidd-2801mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, liver copper levels were increased in adjuvant-induced arthritis in rats during the inflammatory process (68). Another study demonstrated that elevated IL-6 levels resulted in increased levels of ceruloplasmin, the major copper-carrying protein in the blood (69).Therefore, the increase in copper levels could be related to the body's physiological reaction to fight inflammation (68). In addition, the inflammatory disease may be the result of insufficient hepatic copper repositories that cannot support an anti-inflammatory response (70).…”
Section: Prodrug Of β-D-n4-hydroxycytidine (Eidd-2801mentioning
confidence: 98%
“…Copper may also have a role in the immune system response to inflammation (67)(68)(69)(70)(71)(72)(73)(74). In inflammatory conditions, subjects exhibited higher mean serum copper concentrations related to disease activity (67,68).…”
Section: Prodrug Of β-D-n4-hydroxycytidine (Eidd-2801mentioning
confidence: 99%
“…PTP1B is a negative regulator of the insulin metabolic pathway, and α-glucosidase promotes the absorption of carbohydrates into blood vessels by hydrolyzing oligosaccharides to glucose. Despite the identification of many potent compounds [ 38 , 39 , 40 , 41 ], it is still essential to search for new inhibitors with better safety and high efficacy. E. koreanum is used in TCM to treat impotence, female infertility, dysuria, rheumatic arthritis, geriatric depression, and angina pectoris [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, it has been known for some time that saliva contains a group of basic, histidine-rich peptides, histatins, that can bind with copper and are 3–4 kDa in mass [ 74 , 75 , 76 ]. They contain N-terminal amino acid residues that form the “amino terminal Cu(II), Ni(II)” (ATCUN) binding motif, first found in albumin, but bind Cu(II) with lower affinity (Kd in the range of 10 −7 –10 −8 , vs. 10 −11 or lower) [ 74 ].…”
Section: Forms Of Cu In Other Gi Fluids and Their Originsmentioning
confidence: 99%